Inculcating entrepreneurial values in creating business sustainability through business independence in batik craftsmen - Rahayu, Wening Patmi; Hapsari, Novia Tri; Wibowo, Agus; Qodri, Lutfi Asnan; Rusmana, Dede; Narmaditya, Bagus Shandy (Frontiers in Sustainable Cities, 2023)
This research aimed to determine the effect of inculcating entrepreneurial values on business independence and sustainability among 216 batik craftsmen. It also aimed to examine the effect of business independence on business sustainability. Additionally, it intended to determine the impact of entrepreneurial values on business sustainability through business independence. The education of entrepreneurial values that are integrated into business independence is theoretically possible to be one of the strengthening factors for business continuity. 68 samples were selected from the population of batik craft entrepreneurs. The sampling technique uses proportional random sampling. Data were collected using a questionnaire and analyzed with Path Analysis. Entrepreneurial values positively and significantly affect business independence and sustainability. Business independence positively and significantly affects business sustainability. Similarly, entrepreneurial values positively and significantly affect business sustainability through business independence. This research shows that the inculcation of entrepreneurial values has a positive and significant effect both directly and through the mediating variables of business independence. It is proven that the inculcation of entrepreneurial values through business independence has a more significant influence than a direct relationship with business continuity. This research offers insight into the importance of inculcating entrepreneurial values on business sustainability directly and through business independence.